2021
DOI: 10.1126/science.abe6821
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the matrix and viral membrane of HIV-1

Abstract: Gag, the primary structural protein of HIV-1, is recruited to the plasma membrane for virus assembly by its matrix (MA) domain. Gag is subsequently cleaved into its component domains, causing structural maturation to repurpose the virion for cell entry. We determined the structure and arrangement of MA within immature and mature HIV-1 through cryo–electron tomography. We found that MA rearranges between two different hexameric lattices upon maturation. In mature HIV-1, a lipid extends out of the membrane to bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 67 publications
5
83
0
Order By: Relevance
“…In both cases, proteolytic processing would result in a change of the environment of the fluorophore from its packed arrangement within the immature shell. Since mature MA remains associated with the viral membrane and was recently observed to retain a modified lattice arrangement [26], the change in the local microenvironment of eCFP is expected to be less pronounced for HIV eCFP compared to HIV ieCFP , where the released fluorophore would be able to distribute within the particle volume (Figure 1A). To maintain wild-type assembly properties, eCFPtagged HIV-1 plasmids were co-transfected with their untagged counterpart (pCHIV) in an equimolar ratio [27].…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, proteolytic processing would result in a change of the environment of the fluorophore from its packed arrangement within the immature shell. Since mature MA remains associated with the viral membrane and was recently observed to retain a modified lattice arrangement [26], the change in the local microenvironment of eCFP is expected to be less pronounced for HIV eCFP compared to HIV ieCFP , where the released fluorophore would be able to distribute within the particle volume (Figure 1A). To maintain wild-type assembly properties, eCFPtagged HIV-1 plasmids were co-transfected with their untagged counterpart (pCHIV) in an equimolar ratio [27].…”
Section: Resultsmentioning
confidence: 99%
“…Oppositely, depletion of PI(4,5)P2 from the membrane inhibits the release of HIV-1 virions [31]. Finally, a direct interaction of HIV-1 MA with PI(4,5)P2 after the maturation of the viral particle has been documented [26].…”
Section: Fiv Mamentioning
confidence: 99%
“…For HIV-1, it has been suggested that MA/MA interactions mediated by the oligomerization of the Gag polyprotein induce conformational changes that expose this myristoyl group outside the hydrophobic cavity, making it available to interact with the plasma membrane together with the basic patch of helix h1 [11]. Moreover, the reorganization of the MA lattice after the cleavage of HIV-1 Gag also retains the exposure of the myristoyl group and its interaction with the plasma membrane of the infectious particle [26].…”
Section: Fiv Mamentioning
confidence: 99%
“…MA crystallizes on membrane monolayers into a hexameric lattice of trimers [ 84 , 85 ]. Recent work from the Briggs group allowed modeling of the structure of MA within immature and mature HIV-1 particles using MA lattice data derived by cryo-ET ( Figure 3 F) [ 43 ]. This work confirmed the presence of a hexameric lattice of MA in the immature virions and of large holes in the lattice at the six-fold axis, although the lattice was poorly ordered.…”
Section: Ma: Regulator Of Gag-membrane Interactions and Env Incorpora...mentioning
confidence: 99%